Interleukin-17 Promotes Migration and Invasion of Human Cancer Cells Through Upregulation of MTA1 Expression - Guo, Na; Shen, Ge; Zhang, Ying; Moustafa, Ahmed A.; Ge, Dongxia; You, Zongbing (Frontiers in Oncology, 2019)
Interleukin-17 (IL-17) has been shown to promote development of prostate, colon, skin, lung, breast, and pancreatic cancer. The purpose of this study was to determine if IL-17 regulates MTA1 expression and its biological consequences. Human cervical cancer HeLa and human prostate cancer DU-145 cell lines were used to test if IL-17 regulates metastasis associated 1 (MTA1) mRNA and protein expression using quantitative reverse transcription-polymerase chain reaction and Western blot analysis, respectively. Cell migration and invasion were studied using wound healing assays and invasion chamber assays. Thirty-four human cervical tissues were stained for IL-17 and MTA1 using immunohistochemical staining. We found that IL-17 increased MTA1 mRNA and protein expression in both cell lines. Cell migration was accelerated by IL-17, which was abolished by knockdown of MTA1 expression with small interference RNA (siRNA). Further, cell invasion was enhanced by IL-17, which was eliminated by MTA1 knockdown. Human cervical intra-epithelial neoplasia (CIN) and cervical cancer tissues had increased number of IL-17-positive cells and MTA1 expression compared to normal cervical tissues. The number of IL-17-positive cells was positively correlated with MTA1 expression. These findings demonstrate that IL-17 upregulates MTA1 mRNA and protein expression to promote HeLa and DU-145 cell migration and invasion.